2016
DOI: 10.1093/femsle/fnw129
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and effect of rare earth elements on gene expression inMethylosinus trichosporiumOB3b

Abstract: It is well known that Methylosinus trichosporium OB3b has two forms of methane monooxygenase (MMO) responsible for the initial conversion of methane to methanol, a cytoplasmic (soluble) methane monooxygenase and a membrane-associated (particulate) methane monooxygenase, and that copper strongly regulates expression of these alternative forms of MMO. More recently, it has been discovered that M. trichosporium OB3b has multiple types of the methanol dehydrogenase (MeDH), i.e. the Mxa-type MeDH (Mxa-MeDH) and Xox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…The discovery of lanthanides as a cofactor in biotechnologically important organisms other than methylotrophic bacteria expands the possible applications one can envision for REM biomining, bioleaching, and recycling processes (6065). We believe that future research on lanthanide-utilizing enzymes and organisms will improve our understanding of natural and synthetic microbial communities and could provide a basis for novel biotechnological tools and processes.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of lanthanides as a cofactor in biotechnologically important organisms other than methylotrophic bacteria expands the possible applications one can envision for REM biomining, bioleaching, and recycling processes (6065). We believe that future research on lanthanide-utilizing enzymes and organisms will improve our understanding of natural and synthetic microbial communities and could provide a basis for novel biotechnological tools and processes.…”
Section: Discussionmentioning
confidence: 99%
“…In rapid succession, a number of papers documented that the expression of Mxa-MeDH and Xox-MeDH in a variety of methanotrophs and methylotrophs was strongly dependent on the availability of REEs, primarily light REEs (124)(125)(126)(127)(128). In the absence of REEs, little expression of xox genes was observed, while the expression of mxa genes was high.…”
Section: Function Of Rare-earth Elements In Methanotrophsmentioning
confidence: 99%
“…They are, however, the divalent transition metals that form the most stable complexes irrespective of the nature of the ligand, and as such also competitively bind non-cognate metal binding sites with high strength (Foster et al, 2014; Irving and Williams, 1953). Notably, Cu 2+ has also been reported to interfere with REE-dependent regulation of PQQ-dependent methanol dehydrogenases in M. trichosporium OB3b (Gu et al, 2016; Gu and Semrau, 2017), and it is tempting to speculate that mismetallation might be involved in this process, too.…”
Section: Discussionmentioning
confidence: 99%
“…Lanthanides are only poorly available in natural environments (often picomolar concentrations) due to the formation of low soluble hydroxide and/or phosphate (Firsching and Brune, 1991; Meloche and Vrátný, 1959). The presence of active uptake systems to facilitate REE-dependent growth in bacteria has thus been favored by many researchers (Aide and Aide, 2012; Cotruvo et al, 2018; Gu et al, 2016; Gu and Semrau, 2017; Markert, 1987; Picone and Op den Camp, 2019; Tyler, 2004). A transcriptomic study of M. trichosporium OB3b cells observed that multiple genes encoding for different active transport systems were among the most regulated in the presence of cerium (Gu and Semrau, 2017).…”
Section: Introductionmentioning
confidence: 99%